Assisting Disabled Persons in Online Shopping: A Knowledge-Based Process Model - Muhammad Azhar Hussain; Kamran Ahsan; Sarwat Iqbal; Adnan Nadeem; Muhammad Sarim (Journal of Basic & Applied Sciences, 2016)
Knowledge management is gaining more and more attention from business management with a consideration of knowledge as a critical intellectual resource for organization in getting successful competitive advantage. The aim of integrating of KM processes with business processes is to add value, provide supports and increase productivity. The role of technology for knowledge management processes, i.e., capture, codification, dissemination, is very important. Organization are readily adapting e-commerce and shifting business activities over web to maintain competitive advantage and building strong relationship with suppliers, employees, and customers. E-retailing emerged as a new way of shopping; people search/browse products online, compare and purchase with great convenience. It also eliminates barriers that disabled persons encounter when they visit shopping stores such as inaccessible entrance for wheelchair shoppers. However, still there is a significant part of disabled population is neglected from getting benefits of online shopping because of lack of accessibility features in websites. Understanding the knowledge about them can lead business managers to better facilitate in online shopping. This paper proposed a model based on the Nonaka Knowledge Spiral model to support business managers to capture knowledge about disabled person’s online shopping behaviors; supplement this knowledge into their website to support disabled persons. This also helps business managers to capture the un-attended population in their business net.